Formulation and Physicochemical Characterization of a Macroemulsion Containing Ethanolic Extract of Kemuning Leaves (Murraya paniculata (L.) Jack) - Weningtyas, Anditri; Wiratama, Arif Ladika; Wibisono, Taurisma Aulia Nanda; Septiananda, Farsya Hidayah; Prastita, Nenes (Universitas Muhammadiyah Prof. Dr. Hamka, 2026)
Background: Ethanolic extract of Murraya paniculata leaves contains several bioactive constituents, but its direct application is limited by physicochemical instability and solubility issues. Objective: This study aimed to formulate and characterize macroemulsions containing ethanolic extract of Murraya paniculata leaves and to identify the most promising formulation based on physicochemical evaluation. Methods: The extract was prepared by maceration using 96% ethanol. Four macroemulsion formulations were developed using different ratios of virgin coconut oil, Tween 80, PEG 400, and water. The formulations were evaluated through phytochemical screening, organoleptic properties, emulsion type, transmittance, particle size distribution, pH, zeta potential, centrifugation, and cycling test. Results: The extract contained flavonoids, alkaloids, tannins/phenolics, and triterpenoids. All formulations were identified as oil-in-water emulsions. Based on the reported data, F2 showed high transmittance and a low polydispersity index, while F1 and F2 demonstrated better physical stability than F3 and F4. Conclusions: The study indicates that F1 and F2 were the most promising formulations; however, the claim of a single best formulation should be supported by complete, consistently presented particle-size, zeta-potential, and stability data.